Decadal Variation of Atmospheric Rivers in Relation to North Atlantic Tripole SST Mode - Jie Zhang; Yinglai Jia; Rui Ji; Yifei Wu (Atmosphere, 2021)
The North Atlantic tripole (NAT) is the leading mode of sea-surface temperature (SST) in the decadal time scale. Although the NAT is forced by North Atlantic oscillation (NAO), it also has an effect on the atmosphere; for example, the early winter tripole SST signal can influence storm tracks in March. As the NAT not only changes the baroclinicity of the lower layer but also modifies the moisture being released into the atmosphere, we surmise that the NAT has an impact on moisture transport and atmospheric rivers in the decadal time scale. Using ERA5 reanalysis data, the decadal variations in Atmospheric Rivers (ARs) in the North Atlantic in boral winter in relation to NAT phases were studied. During the positive NAT phase, the positive SST in the central and western North Atlantic increases the humidity and causes an anticyclonic wind response, which enhances the northeastward transport of moisture. As a result, ARs tend to be longer and transport more moisture toward northwestern Europe. This causes enhanced extreme rain in the UK and Norway. During the negative NAT phase, the positive SST anomalies in the south and east of the North Atlantic provide more moisture, induce a southward shift of the ARs and enhance extreme rain in the Iberian Peninsula. The Gulf Stream (GS) front is stronger during the negative NAT phase, increasing the frequency of the atmospheric front and enlarging the rain rate in ARs.